MicroRNAs as Potential Biomarkers for the Diagnosis of Chronic Kidney Disease: A Systematic Review and Meta-Analysis - Li, Jing; Ma, Leilei; Yu, Hangxing; Yao, Yahong; Xu, Zhiyuan; Lin, Wei; Wang, Lin; Wang, Xuejun; Yang, Hongtao (Frontiers in Medicine, 2022)
For Chronic Kidney Disease, the study of microRNA as a biomarker has become an exciting area, so we carried out a meta-analysis to investigate the potential diagnostic values of miRNAs in CKD. We searched Pubmed, Cochrane Library, Embase, and Web of science databases to identify relevant publications published from the establishment of the database to April 30, 2021. We included a total of 26 articles containing 56 studies. There were 4098 patients with CKD and 2450 patients without CKD. We found that the overall sensitivity and specificity of miRNAs in CKD diagnosis were 0.86(95% CI: 0.83-0.89), 0.79 (95% CI: 0.75-0.83). In addition, we plotted the summary receiver operator characteristic (SROC) curve to assess diagnostic accuracy, with the area under the curve (AUC) of 0.90 (95% CI: 0.87-0.92). Subgroup analysis showed that sensitivity, specificity, and AUC of miRNAs in plasma and serum was 0.84, 0.78, 0.88; 0.79, 0.76,0.83, respectively. While miRNAs in urine was 0.89 for sensitivity,0.82 for specificity,and 0.92 for AUC,respectively. Moreover, we found that the panel of miRNAs could improve the pooled sensitivity (0.88, 0.81 and 0.91 for sensitivity, specificity and AUC).We believe that miRNAs have great potential to become an effective diagnostic biomarker for CKD. Panels of miRNA have higher accuracy than single miRNAs.Additionally, miRNA in both blood and urine have a significant accuracy in the diagnosis of CKD, nevertheless, urine is superior.